MODERN THEORIES IN THE ETIOLOGY OF ULCERATIVE COLITIS: A LITERATURE REVIEW - Kaymanova Kamila Imamovna (Modern American Journals, 2025)
Ulcerative colitis (UC), a chronic inflammatory condition of the colon, remains a subject of extensive research due to its complex and multifactorial etiology. Over the past 10–15 years, significant progress has been made in understanding the interplay between genetic predisposition, environmental influences, gut microbiota, immune dysregulation, and epithelial barrier dysfunction in the development of UC. This literature review critically examines contemporary theories explaining UC pathogenesis, highlighting recent findings in genomics, microbiome research, and immunological mechanisms. By analyzing recent scholarly contributions, this paper aims to synthesize current perspectives and identify emerging trends in UC etiology, ultimately contributing to more effective strategies for prevention and treatment.
Keywords: Ulcerative colitis, inflammatory bowel disease (ibd), gut microbiota, immune dysregulation, genetic susceptibility, environmental factors, intestinal barrier